2003
DOI: 10.1002/ejoc.200300149
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of β‐L‐Rhamnosidic Linkages by the 2‐Ulosyl Donor Approach: Synthesis of a Trisaccharide with a Central β‐L‐Rhamnose Unit

Abstract: Practical procedures for the production of variously blocked 6‐deoxy‐α‐L‐arabino‐2‐ketohexosyl bromides from L‐rhamnose have been developed. These compounds are highly useful as indirect β‐L‐rhamnosyl donors: they undergo β‐specific glycosidations under Koenigs‐Knorr conditions, and the 2‐keto group of the resulting 6‐deoxy‐β‐L‐hexosiduloses is reduced with high β‐L‐rhamno selectivity. The straightforward application of this 2‐ulosyl donor approach for the synthesis of β‐L‐rhamnose‐containing di‐ and trisaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Often the reduction is very selective due to (non)­chelation to α-neighboring groups and 1,3-diaxial interactions. ,, Following this route Collins and Overend prepared 6-deoxy- l -taloside 533 (Scheme a). First, the free hydroxyl 531 was oxidized to the 2-uloside 532 followed by stereoselective hydrogenation using Adams’ catalyst which after hydrolysis and peracetylation afforded 6-deoxy- l -taloside 533 . , In a search for a good method for the preparation of the difficult β- l -rhamnosides, Lichtenthaler and co-workers found that 2-ulosyl bromides like 535 gave excellent β-selectivity for both isopropanol (e.g., to 536 ) and sugar acceptors upon activation with silver carbonate (Scheme b). The 2-ulosyl bromide 535 was prepared by treatment of the acyloxy- l -rhamnal 534 with N -bromosuccinimide (NBS). The reduction of the uloside 536 was affected by NaBH 4 , giving rise to the axial anomer 537 with high stereoselectivity.…”
Section: Synthesis Of 6-deoxy-l-hexoses From Carbohydratesmentioning
confidence: 99%
“…Often the reduction is very selective due to (non)­chelation to α-neighboring groups and 1,3-diaxial interactions. ,, Following this route Collins and Overend prepared 6-deoxy- l -taloside 533 (Scheme a). First, the free hydroxyl 531 was oxidized to the 2-uloside 532 followed by stereoselective hydrogenation using Adams’ catalyst which after hydrolysis and peracetylation afforded 6-deoxy- l -taloside 533 . , In a search for a good method for the preparation of the difficult β- l -rhamnosides, Lichtenthaler and co-workers found that 2-ulosyl bromides like 535 gave excellent β-selectivity for both isopropanol (e.g., to 536 ) and sugar acceptors upon activation with silver carbonate (Scheme b). The 2-ulosyl bromide 535 was prepared by treatment of the acyloxy- l -rhamnal 534 with N -bromosuccinimide (NBS). The reduction of the uloside 536 was affected by NaBH 4 , giving rise to the axial anomer 537 with high stereoselectivity.…”
Section: Synthesis Of 6-deoxy-l-hexoses From Carbohydratesmentioning
confidence: 99%
“…Since reduction of the β-d-glycosiduloses formed is highly manno-selective, [3,6] the two-step-sequence, 2 Ǟ 5 Ǟ 6, has evolved into an expedient procedure for the generation of β-d-mannosides, the ''ulosyl donor approach'', which has successfully been applied to the synthesis of β-d-mannose-oligosaccharides up to the hexasaccharide level, [3,7] as well as to the generation of β-lrhamnosidic linkages. [8] A gluco-selective reduction may also be accomplished in a straightforward manner by using borane as the reductant, e.g. 5 Ǟ 7, providing 2-OH-free β-d-glucosides.…”
Section: Introductionmentioning
confidence: 99%
“…In similar manner, we have prepared the 6-deoxy enone N -glycoside derivative 3n , which has various possible synthetic and biochemical applications. The starting 2,3,4-tri- O -acetyl-6-deoxy- l -rhamnal 1b was synthesized from l -rhamnose according to a literature reported procedure (Scheme ). , …”
mentioning
confidence: 99%